2018
DOI: 10.1099/mic.0.000599
|View full text |Cite
|
Sign up to set email alerts
|

The algal chloroplast as a synthetic biology platform for production of therapeutic proteins

Abstract: The chloroplast of Chlamydomonas reinhardtii and other microalgae represents an attractive new platform for the synthesis of recombinant therapeutics using synthetic biology (synbio) approaches. Transgenes can be designed in silico, assembled from validated DNA parts and inserted at precise and predetermined locations within the chloroplast genome to give stable synthesis of a desired recombinant protein. Numerous recent examples of different therapeutic proteins produced successfully in the C. reinhardtii chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 83 publications
1
96
0
Order By: Relevance
“…Efforts to express human therapeutic proteins in photosynthetic microorganisms abound in the literature. In their preponderance, these entail heterologous transformation of microalgal chloroplasts as a synthetic biology platform for the production of biopharmaceutical and therapeutic proteins (Dyo and Purton, 2018, and references therein). The vast majority of such efforts have employed transformation of the chloroplast in the model green microalga Chlamydomonas reinhardtii via double homologous recombination of exogenous constructs encoding heterologous proteins (Demain and Vaishna, 2009;Surzycki et al, 2009;Tran et al, 2009;Coragliotti et al, 2011;Gregory et al, 2013;Jones and Mayfield, 2013;Rasala and Mayfield, 2015;Baier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to express human therapeutic proteins in photosynthetic microorganisms abound in the literature. In their preponderance, these entail heterologous transformation of microalgal chloroplasts as a synthetic biology platform for the production of biopharmaceutical and therapeutic proteins (Dyo and Purton, 2018, and references therein). The vast majority of such efforts have employed transformation of the chloroplast in the model green microalga Chlamydomonas reinhardtii via double homologous recombination of exogenous constructs encoding heterologous proteins (Demain and Vaishna, 2009;Surzycki et al, 2009;Tran et al, 2009;Coragliotti et al, 2011;Gregory et al, 2013;Jones and Mayfield, 2013;Rasala and Mayfield, 2015;Baier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many genetic elements have been characterized in, or adapted to, microalgae. Several recent reviews have been published on algal synthetic biology and chloroplast genome modification (Doron et al, 2016;Scaife and Smith, 2016;Dyo and Purton, 2018;Poliner et al, 2018). Therefore, we will focus here on new developments and on nuclear genetic elements.…”
Section: Genetic Partsmentioning
confidence: 99%
“…DNA transformation of the algal chloroplast has been reported for a handful of species, but the technology is most advanced for C. reinhardtii [11]. Numerous studies have shown that insertion of foreign DNA into the plastome occurs exclusively via homologous recombination allowing precise and predictive targeting of transgenes into specific loci [12].…”
mentioning
confidence: 99%
“…Our survey of the literature has revealed that over 100 different foreign proteins have been produced successfully in the C. reinhardtii chloroplast. These include a wide range of therapeutic proteins such as vaccines, hormones and antibodies [11]; industrial enzymes [15,16], and enzymes for synthesizing novel metabolites in the organelle [17][18][19][20][21]. However, in almost all cases the genetic engineering has involved the insertion of just one transgene (or a single transgene together with a bacterial gene such as aadA or aphA-6 as the selectable marker [13]).…”
mentioning
confidence: 99%